Construction of Cellulose Binding Domain Fusion FMN-Dependent NADH-Azoreductase and Glucose 1-Dehydrogenase for the Development of Flow Injection Analysis with Fusion Enzymes Immobilized on Cellulose - Yano, Shigekazu; Hori, Yukari; Kijima, Tatsuro; Konno, Hiroyuki; Suyotha, Wasana; Takagi, Kazuyoshi; Wakayama, Mamoru (Journal of applied glycoscience : JAG, 2019)
The cellulose binding domain (CBD) of cellulosome-integrating protein A from Clostridium thermocellum NBRC 103400 was genetically fused to FMN-dependent NADH-azoreductase (AZR) and glucose 1-dehydrogenase (GDH) from Bacillus subtilis. The fusion enzymes, AZR-CBD and CBD-GDH, were expressed in Escherichia coli Rosetta-gami B (DE3). The enzymes were purified from cell-free extracts, and the specific activity of AZR-CBD was 15.1 U/mg and that of CBD-GDH was 22.6 U/mg. AZR-CBD and CBD-GDH bound strongly to 0.5 % swollen cellulose at approximately 95 and 98 % of the initial protein amounts, respectively. After immobilization onto the swollen cellulose, AZR-CBD and CBD-GDH retained their catalytic activity. Both enzymes bound weakly to 0.5 % microcrystalline cellulose, but the addition of a high concentration of microcrystalline cellulose (10 %) improved the binding rate of both enzymes. A reactor for flow injection analysis was filled with microcrystalline cellulose-immobilized AZR-CBD and CBD-GDH. This flow injection analysis system was successfully applied for the determination of glucose, and a linear calibration curve was observed in the range of approximately 0.16–2.5 mM glucose, with a correlation coefficient, r, of 0.998.